The Impact of Message Framing on Wildlife Approach During Ungulate Viewing Experiences in the Greater Yellowstone Ecosystem. Issue 1 (April 2023) - Freeman, Stephanie; Taff, Brendan Derrick; Lawhon, Ben; Benfield, Jacob A.; Kreye, Melissa; Newton, Jennifer; Miller, Lauren; Newman, Peter
Every year, millions of people visit parks and protected areas to view wildlife. Conflict between people and ungulates is prominent, and many incidents occur when people approach ungulates at proximities less than the National Park Service regulation of 25 yards. The purpose of this study was to test how wildlife viewing communication messages impact park visitors' approach behavior. A survey and walking exercise were conducted with life-sized ungulate cutouts on a 100-yard transect in Grand Teton and Yellowstone National Parks to test the influence of three message frames (i.e., current NPS messaging, resource protection messaging, and a visitor experience message) on visitors' approach behaviors. Park visitors overestimated proximity when given current park messaging. Additionally, the resource protection- and the visitor experience-framed messages led to more conservative wildlife approach compared to current park messaging. These results have practical applications for influencing visitors' behaviors and reducing human-wildlife conflict through education and interpretation.